Morphometric Comparison of the Pterional Trans-Sylvian and the Pretemporal Trans-Clinoidal Approaches to the Posterior Communicating Artery. Issue 1 (29th August 2020) - Basma, Jaafar; Moore, Kenneth A; Krisht, Khaled; Abuelem, Tarek; Arnautovic, Kenan; Michael, L Madison; Aboud, Emad; Krisht, Ali F
Abstract: BACKGROUND: Posterior communicating (Pcom) aneurysms in the modern era have tended toward increased complexity and technical difficulties. The pretemporal approach is a valuable extension to the pterional approach for basilar apex aneurysms, but its advantages for Pcom aneurysms have not been previously elucidated. OBJECTIVE: To quantify characteristics of the pretemporal approach to the Pcom. METHODS: We dissected 6 cadaveric heads (12 sides) with a pretemporal transclinoidal approach and measured the following variables: (1) exposed length of internal carotid artery (ICA) proximal to the Pcom artery; (2) exposed circumference of ICA at the origin of Pcom; (3) deep working area between the optic nerve and tentorium/oculomotor nerve; (4) superficial working area; (5) exposure depth; and (6) the frontotemporal (superior posterolateral) and (7) orbito-sphenoidal (inferior anterolateral) angles of exposure. RESULTS: Compared with pterional craniotomy, the pretemporal transclinoidal approach increased the exposed length of the proximal ICA from 3.3 to 11.7 mm ( P = .0001) and its circumference from 5.1 to 7.8 mm ( P = .0003), allowing a 210° view of the ICA (vs 137.9°). The deep and superficial working areas also significantly widened from 53.7 to 92.4 mm 2 ( P = .0048) and 252.8 to 418.2 mm 2 ( P = .0001), respectively; the depth of the exposure was equivalent. The frontotemporal and spheno-Sylvian angles increased by 17° ( P = .0006) and 10° ( P = .0037), respectively. CONCLUSION: The pretemporal approach can be useful for complex Pcom aneurysms by providing easier proximal control, wider working space, improved aneurysm visualization, and more versatile clipping angles. Enhanced exposure results in a potentially higher rate of complete aneurysm obliteration and complication avoidance.